1995
DOI: 10.1063/1.360322
|View full text |Cite
|
Sign up to set email alerts
|

Resonant cavity enhanced photonic devices

Abstract: We review the family of optoelectronic devices whose performance is enhanced by placing the active device structure inside a Fabry-Perot resonant microcavity. Such resonant cavity enhanced (RCE) devices benefit from the wavelength selectivity and the large increase of the resonant optical field introduced by the cavity. The increased optical field allows RCE photodetector structures to be thinner and therefore faster, while simultaneously increasing the quantum efficiency at the resonant wavelengths. Off-reson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
227
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 634 publications
(230 citation statements)
references
References 146 publications
2
227
1
Order By: Relevance
“…Its effective implementation requires additional on-chip optical elements redirecting the light from horizontal waveguides to vertical resonant cavities. On the other hand, the advantage of vertical configuration is the opportunity of the application of distributed Bragg reflectors based on semiconductor heterostructures as the resonator mirrors [34]. Such reflectors are characterized by the adaptability to streamlined manufacturing.…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its effective implementation requires additional on-chip optical elements redirecting the light from horizontal waveguides to vertical resonant cavities. On the other hand, the advantage of vertical configuration is the opportunity of the application of distributed Bragg reflectors based on semiconductor heterostructures as the resonator mirrors [34]. Such reflectors are characterized by the adaptability to streamlined manufacturing.…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…If β = 1, the peak quantum efficiency of such devices at the resonance wavelengths can be calculated as follows [34]:…”
Section: Models and Simulation Methodsmentioning
confidence: 99%
“…The development of photodiode devices on micro and nanophotonic structures has opened new possibilities over the standard technology. The impinging light is strongly confined inside those photonic structures enhancing the photocarrier generation, as it has been observed in nanowire resonators 2,3 and in the electrooptical response of the optical cavities [4][5][6] . Simultaneously, photoexcited carriers are generated close to the collecting electrodes, boosting the power generation in photovoltaic cells [7][8][9][10][11] .…”
mentioning
confidence: 90%
“…The resonant-cavity detector design [24] is another technique that can be applied to Si detectors [25]- [27] to improve efficiency while maintaining a thin absorbing layer. Schaub et al [27] reported an example of such detectors that utilized Si laterally grown over a Si/SiO 2 Bragg reflecting mirror stack.…”
Section: Soi Detectorsmentioning
confidence: 99%